PATTERN FORECASTING OF PERFORMANCE INDICES FOR AIR-AND-SCREEN CLEANER FROM CHAFFING EFFICIENCY RISE - Yury Ivanovich Yermolyev; Andrey Vladimirovich Butovchenko; Artem Alexandrovich Doroshenko (Advanced Engineering Research)
The interrelation of the chaffing process efficiency growth and the air - screen grain - cleaner perfo r mance indices is considered. A mathematical functional model of the air separator and the screen clea n er is described as a closed loop quasi - static system. Agronomical performance indices of the machine are accepted as criteria. Through vari ation of the delivery, technological properties of the basic material and of the c ompleteness of each component sep aration, the rational values of the control factor arguments are revealed, the numerical results of t he grain loss ma gnitude, completeness of the foreign and other grain separation, as well as their content in the puri fied material, are determined. The developed mathematical model of the heterogenic granular medium chaffing allows — through the known parametric and structural synthesis methods — conducting a multivariate analysis of the process and eval uating the air separat or rational parameters for the specified conditions and the restrictions to its performance ind ices. As a result of modeling, a trend of the index variation of the machine performance and their in terrelation is r e vealed. The obtained results have shown a s ignificant increase in productivity and technological parameters of the similar machine performance from the efficiency growth of their air separator.